Isolation, characterization and liposome-loaded encapsulation of a novel virulent Salmonella phage vB-SeS-01 - Luo, Yuhang; Mahillon, Jacques; Sun, Lin; You, Ziqiong; Hu, Xiaomin (Frontiers in Microbiology, 2025)
IntroductionSalmonella is a common foodborne pathogenic bacterium, displaying facultative intracellular parasitic behavior, which can help the escape against antibiotics treatment. Bacteriophages have the potential to control both intracellular and facultative intracellular bacteria and can be developed as antibiotic alternatives.MethodsThis study isolated and characterized vB-SeS-01, a novel Guernseyvirinae phage preying on Salmonella enterica, whose genome is closely related to those of phages SHWT1 and vB-SenS-EnJE1. Furthermore, nine phage-carrying liposome formulations were developed by film hydration method and via liposome extruder.Results and DiscussionPhage vB-SeS-01 displays strong lysis ability against 9 out of 24 tested S. enterica strains (including the pathogenic “Sendai” and “Enteritidis” serovars), high replicability with a burst size of 111 ± 15 PFU/ cell and a titre up to 2.1 × 1011 PFU/mL, and broad pH (4.0 ~ 13.0) and temperature (4 ~ 80°C) stabilities. Among the nine vB-SeS-01 liposome-carrying formulations, the one encapsulated with PC:Chol:T80:SA = 9:1:2:0.5 without sonication displayed the optimal features. This formulation carried up to 1011 PFU/mL, with an encapsulation rate of 80%, an average size of 172.8 nm, and a polydispersity index (PDI) of 0.087. It remained stable at 4°C and 23°C for at least 21 days and at 37°C for 7 days. Both vB-SeS-01 and vB-SeS-01-loaded liposomes displayed intracellular antimicrobial effects and could reduce the transcription level of some tested intracellular inflammatory factors caused by the infected S. enterica sv. Sendai 16,226 and Enteritidis 50041CMCC.